Inhibition of Atherosclerotic Plaque Development by Oral Administration of α-Glucosyl Hesperidin and Water-Dispersible Hesperetin in Apolipoprotein E Knockout Mice. (2nd January 2019) - Sugasawa, Noriko; Katagi, Ayako; Kurobe, Hirotsugu; Nakayama, Taisuke; Nishio, Chika; Takumi, Hiroko; Higashiguchi, Fumiharu; Aihara, Ken-ichi; Shimabukuro, Michio; Sata, Masataka; Kitagawa, Tetsuya
Abstract: Objective: Hesperidin, an abundant flavonoid in citrus fruit, and its aglycone, hesperetin, have been reported to possess various physiological activities, including antioxidant, anti-inflammatory, hypolipidemic, and antihypertensive activities. In this study, we investigated whether α-glucosyl hesperidin and water-dispersible hesperetin have protective effects on atherosclerotic progression in apolipoprotein E knockout (Apo-E KO) mice. Methods: Ten-week-old male Apo-E KO mice were randomly assigned a regular high-fat diet, a high-fat diet with 0.5% α-glucosyl hesperidin, or a high-fat diet with 0.1% water-dispersible hesperetin for 12 weeks. Measurement of plasma total cholesterol levels, histological staining of aortic root, and immunohistochemistry for macrophages were performed to evaluate atherosclerotic plaque formation. Vascular reactivity of mouse aortic rings was also measured. Results: Both α-glucosyl hesperidin and water-dispersible hesperetin reduced plasma total cholesterol level. They also reduced plaque formation area, adipose deposition, and macrophage infiltration into atherosclerotic lesion. Vascular-endothelium-dependent relaxation in response to acetylcholine was improved in both experimental diet groups compared to the high-fat diet group. Conclusions: Our study suggests that both α-glucosyl hesperidin and water-dispersible hesperetin exert protective effects on atherosclerotic progression in Apo-E KO mice because they exhibit hypolipidemic activity, reduce inflammation through macrophages, and prevent endothelial dysfunction.